2005
DOI: 10.1097/01.mat.0000169121.09075.53
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Heparin-Binding AN69 ST Hemodialysis Membrane: II. Clinical Studies without Heparin Administration

Abstract: Binding polyanionic unfractionated heparin over the modified AN69 polyacrylonitrile membrane, the surface electronegativity of which has been neutralized by polyethyleneimine (AN69-ST), renders the membrane more hemocompatible. This property was tested in two groups of long-term hemodialysis patients. Results were rated as massive or partial clotting of a dialyzer at the end of the session. Group I patients were included in a prospective, cross-over study comparing standard dialysis with hemodialysis without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 12 publications
1
35
1
Order By: Relevance
“…A complete occlusion of the extracorporeal system was seen in only 1.5% of 66 treatment sessions [7] and in 2% of 331 sessions in patients at high risk of bleeding and without additional heparinization during dialysis [9] . In these studies, however, patients were not treated with oral anticoagulants and coagulation disorders were exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A complete occlusion of the extracorporeal system was seen in only 1.5% of 66 treatment sessions [7] and in 2% of 331 sessions in patients at high risk of bleeding and without additional heparinization during dialysis [9] . In these studies, however, patients were not treated with oral anticoagulants and coagulation disorders were exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [6], Jiang et al [7] and Huang et al [8,9] also improved blood compatibilities of the poly(vinylidene fluoride), polyethylene (PE) and PSF membranes by covalent attachment of heparin [6][7][8][9]. In vivo tests carried out with commercial hemodialysis membranes, AN69 ST, HEMOPHAN and EVODIAL showed that it is possible to reduce systemic administration of heparin through its immobilization on these membranes [10][11][12][13][14][15]. On the other hand, one clinical study reported that heparin coated AN69 ST membrane does not reduce clotting during hemodialysis when compared to a conventional PSF filter [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used approach is to mimic endothelial cell layer by heparin immobilization. The beneficiary effect of heparin coatings on the membranes has been reported by many authors both in vitro [1][2][3][4][5][6][7][8][9] and in vivo [10][11][12][13][14][15]. For example, Cheung et al [1] observed that complement activation induced by hemodialysis can be modulated with heparin immobilized cellulose acetate membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heparin grafting is stable and does not get released in the blood. Hence, a local anticoagulation effect with a reduced requirement for or even the elimination of systemic anticoagulation may be possible [8]. …”
Section: Introductionmentioning
confidence: 99%